Upaya Pelestarian Kosistem Pesisir Melalui Penanaman Mangrove di Kawasan Wisata Luppung, Desa Manyampa, Kabupaten Bulukumba - Fahrul Fahrul; Ilham Jaya; Muhammad Dalvi Mustafa; Marlina Ahmad (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2023)
Mangrove forest ecosystem is an important habitat for marine organisms and as a coast guard from abrasion. One area that has mangrove forests and is quite vulnerable to abrasion is Luppung Hamlet,  Manyampa  Village  in  Bulukumba  Regency.  This  activity  aims  to  increase  public awareness about the importance of mangroves in preventing abrasion, especially in the Luppung tourist area, Manyampa Village. This activity involves the village government, local government, village youths who are members of village organizations, and village residents. In general, this activity went smoothly and was followed with high enthusiasm by all participants. It is hoped that with this activity, the community around the tourist area can understand and take advantage of the great benefits possessed by mangroves and prevent Manyampa Village, especially in Luppung Hamlet from abrasion.